PENGARUH MODEL PEMBELAJARAN VCT (VALUE CLARIFICATION TECHNIQUE) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PKN KELAS IV SEKOLAH DASAR: PENGARUH MODEL PEMBELAJARAN VCT (VALUE CLARIFICATION TECHNIQUE) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PKN KELAS IV SEKOLAH DASAR - ratna herawati; treny hera; Dian Nuzulia armariena (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The purpose of this study was to determine whether there was an effect of the VCT (Value Clarification Technique) model on learning outcomes of PKN grade IV elementary school. The method used in this research is the True Experimental Design type Experiment method in the form of Posttest Only Control Group Design. The population in this study used purposive sampling, namely class IV A and IV B. Data collection techniques were through tests, observation, documentation. Based on the research results and data analysis, it can be seen that the experimental class which was treated with the VCT (Value Clarification Technique) model had an average final score of 80.00 higher than the control class which was given treatment without using the VCT (Value Clarification Technique) model. technique) that is equal to 49.5. The results of testing the hypothesis obtained tcount = 7.561 and ttable 2.018, tcount > ttable (7.561 > 2.018) this was then compared with the ttable value of the confidence level ɑ = 5% (0.05), then H0 was rejected and Ha was accepted to conclude that there was a Model Effect Learning VCT (Value Clarification Technique) on Learning Outcomes in PKN Class IV Elementary School Subjects.